Education and the Economy of Attention in Times of (Post-) Pandemic (European Journal of Social Science Education and Research, 2022)
With the Coronavirus crisis, online teaching seems to have become a norm in Higher Education. The essay argues that, although this new pedagogical practice is totally acceptable in times of social distancing, it can lead to something more radical, especially with the strong will of HE institutions to continue this mode of teaching beyond the period of crisis. The normalisation of dematerialised teaching comes as a challenge to academics: it is imbedded in a new form of economy, where attention is a key source of value and labour. The omnipresence of virtual interfaces questions the very fabric of their practice as teachers, especially in humanities, where it can lead to an intensification of the pauperization of teaching staffs, due to forced redundancy. To understand how the normalisation of online teaching after the crisis can be potentially noxious, the essay proceeds by looking at the change of agency of digital tools in teaching contexts, through the concept of pharmakon, developed by Bernard Stiegler, that offers the chance for a critique of this new pedagogical strategy which can be positive during the crisis, but potentially destructive after. This concept leads to a new criteria of judgment of the digital (mode of teaching), which has to be understood as a third way between the optimism of managerial perspectives, always keen to consider information technologies as the perfect catalyst for neo-liberal reforms in education; and the traditional technophobia, proper to a philosophical tradition that, from the Frankfurt School to Giorgio Agamben, apprehends the mediation of technology essentially as a critical regression and a modern form of rationalisation that engenders an immense social and psychic alienation.